Big Pig on a dig - Cox, Phil Roxbee; Tyler, Jenny; Cartwright, Stephen, 1947-2004 (Tulsa, Okla. : EDC Pub., 2006)
Pig finds a treasure map and digs for gold.
Usborne Phonics Readers.
Created in consultation with a language expert, this book is part of a phonics-based series written to help children learn to read.
Originally published: London : Usborne, 2006.
Lift-the-flap book.
Keywords: Swine -- Juvenile fiction; Vocabulary; Pigs -- Fiction; Toy and movable books; Readers